Energy and Climate Change Policies of Russia and China - Yesevi, Çağla Gül (New Castle: Cambridge Scholars Publishing, 2014)
The article entitled “Energy and Climate Change Policies of Russia The article entitled Energy and Climate Change Policies of Russia and China” by Çağla Gül Yesevi and Ceren Uysal Oğuz aims to analyse the meaning and dimensions of glabal cliamate change, energy and environmental policies of Russia and China.
Keywords: Climate Change; Energy Policies; Russia; China; İklim Değişikliği; Enerji Politikaları; Rusya; Çin